(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper examines the emotional and cultural struggles depicted in Chitra Banerjee Divakaruni’s novel Sister of My Heart. Focusing on the lives of cousins Anju and Sudha Chatterjee, the paper explores how their deep bond endures despite the geographical separation and the challenges of migration. The narrative reveals the intense emotional toll of displacement, as both women grapple with feelings of alienation, longing for their homeland, and the fading memories of their cultural roots. The paper highlights how their journey in America exposes them to discrimination and marginalization, further complicating their efforts to adapt and find a sense of belonging. Special attention is given to the unique struggles faced by diasporic women, who often bear the brunt of cultural dislocation and emotional turmoil. Through an analysis of Anju and Sudha’s evolving identities and relationships, this paper portrays the resilience and adaptability required to navigate the complex terrain of a new cultural landscape. By situating the novel within the broader framework of diasporic literature, the paper aims to illuminate the transformative journey of self-discovery and the quest for identity amidst cultural disparity and emotional disintegration.